Pengaruh Gamifikasi dan Reputasi terhadap Penggunaan Platform E-Commerce Indonesia - Shanata Bakti, Maura; Diaz Ferdiansyah, Alfarel; Rizki Abyan, Naufal; Rahma Aulia, Virdha (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2026)
The rapid development of e-commerce in Indonesia has driven platforms such as Shopee to adopt innovative strategies to enhance user engagement and loyalty. This study investigates the influence of gamification and reputation on platform usage and repurchase intention in the Indonesian e-commerce context. The topic was chosen due to the growing competition in digital markets and the necessity for platforms to retain their users. A quantitative approach was used, with data collected via an online questionnaire distributed to 98 active Shopee users through convenience sampling. Data analysis was conducted using Structural Equation Modeling with a Partial Least Square (SEM-PLS) approach. The results indicate that gamification has a significant positive effect on user intention and platform usage, while reputation influences trust in vendors and repurchase intention. Moreover, platform usage acts as a mediating variable between gamification, reputation, and repurchase intention. These findings highlight the critical role of interactive features and perceived credibility in fostering user loyalty. In conclusion, gamification and platform reputation are key determinants in sustaining customer retention within Indonesia’s competitive e-commerce landscape.